ADOPSI DALAM HUKUM ISLAM DAN HUKUM INDONESIA - Sainul, Sainul (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2015)
This essay reveal about the procedure of adoption (adoption) in accordance with Islamic law and the legal status of adopted children in force in Indonesia. In Law No. 23 of 2002 on Child Protection determined that the removal of the child should not be decided in religion and blood relationship with the adoptive child's biological parents. Setting Government Regulation No. 54 Year 2007 on the Implementation of Child Adoption namely that the procedures for adoption between Indonesian citizen that a child can lift a maximum of 2 (two) times the distance of at least 2 (two) years. For the validity of the appointment of a child in Indonesia, after a request for adoption through the procedures of the rules in the legislation that exists, adoptions subsequently passed through the last step, namely the presence of a court decision issued by the court in the form of a court warrant or known by the judgment declaratory, that statement from judges that the adopted child is legitimate as a foster child of the adoptive parents who apply for adoption. Court decisions also covers the legal status of the adopted child in the family. The concept of appointment of a child in Islamic law does not recognize adoption of children in the sense of being a child of the absolute, being that there are only allowed or susruhan to maintain with the aim of treating the child in terms of love of giving a living, education or services in all the needs that are not treated as biological children ( nasab). In the Islamic concept, the appointment of a child should not be cut off nasab between the child with his biological parents is based on the Qur'an Surat Al-Ahzab verse 4,5,37, and 40. This was later associated with the legal consequences arising is about marriage and inheritance system. In marriage a priority nasab guardian for girls is his own father. In inheritance, adopted children does not include the heirs and vice versa, which amount is 1/3 (one third) part of the legacy.